Living coralligenous as geo-historical structure built by coralline algae - Basso, Daniela; Bracchi, Valentina Alice; Bazzicalupo, Pietro; Martini, Marco; Maspero, Francesco; Bavestrello, Giorgio (Frontiers in Earth Science, 2022)
The most important reef of the Mediterranean is the Coralligène (Coralligenous = C), including several types of calcareous algal-invertebrate build-ups growing in normal open marine conditions. We analysed and compared two C samples from the Ligurian Sea developed in different environmental settings: 1) off Portofino on a rocky cliff, at about 40 m depth; 2) in front of Bogliasco, on a sub-horizontal substrate at 10 m depth. The maximum AMS radiocarbon dating provided an older age for Bogliasco (about 5 ka BP) than for Portofino (about 3.6 ka BP) and the mean accumulation rate of the Portofino build-up (about 80 µm y-1) resulted higher than the one in Bogliasco (about 65 µm y-1). The different sides of each build-up showed a remarkable heterogeneity in the dominant cover by living organisms, and the comparison between the two build-ups highlighted an evident diversity in their taxonomic composition and structure, although crustose coralline algae (CCA) are the dominant framework builder and major autogenic ecosystem engineers at both localities, in the present as in the past millennia. Other major components of the structure are bryozoans and serpulids, and an important role is played by sediment filling. In Bogliasco, extreme climate events and major peaks of fine matrix and terrigenous grains are observed, lithologically related to the drainage basin of the Poggio creek, and associated with charophytes occurrence and reduced CCA abundance. The occurrence of the rare Sporolithon ptychoides was observed, both in Portofino at about 750 BCE, and in Bogliasco. These Sporolithon phases are likely related with warm and humid spells punctuating the Holocene climate fluctuations in the Ligurian Sea. Because coralline algae are confirmed to be the most important habitat engineer of the Mediterranean reefs, they deserve more attention in the framework of any monitoring initiative aimed at C management and conservation.